Get connected - Dillon, Ann G. (Wadsworth, 2008)
Tired of feeling unprepared for class or unsure of your study skills? GET CONNECTED: STUDY SKILLS connects you the tools you need to get ahead, whether you just need to brush up or if you're falling behind. From how to take notes more effectively to strategies for taking exams, GET CONNECTED shows you how to get better grades and learn habits that lead to success. Don't wait to live and learn; get the textbook that helps you get ahead. Get connected today!